KEBUDAYAAN PADA NOVEL “WEDDING AGREEMENT” DENGAN NOVEL “HATI SUHITA” (KAJIAN SASTRA BANDING) - Rahmawati, Novia; Utari Dewi, Trie (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2024)
The aim of this research was to see the cultural comparison of the novel Wedding Agreement by Mia Chuz and the novel Hati Suhita by Khilma Anis. The method used in this research is descriptive qualitative with a comparative literary approach. The results of this research show that there are similarities and differences between the two novels in aspects of the nature of human life in the categories of suffering and happiness, besides that there are also aspects of the nature of human work and the nature of human time in the categories of present and past. As for aspects of the nature of human time in the future category, there are no differences in cultural aspects in the two novels. The conclusion of the comparative study of cultural aspects is that there are similarities and differences in every aspect of the two novels, except for differences in aspects of the nature of human time in the future category.